Study on synthesis and the reaction mechanism of polybenzoxazine-silica nanocomposites provided from perhydropolysilazane. (2nd September 2016) - Lee, Joo Yeon; Takeichi, Tsutomu; Saito, Reiko
Abstract: Polybenzoxazine/silica nanocomposites were synthesized with perhydropolysilazane (PHPS) and benzoxazines via thermal polymerization in one step. The reaction of benzoxazine's hydroxy group and PHPS was investigated via 1 H nuclear magnetic resonance and Fourier transform infrared spectrometry. At low heating temperatures, benzoxazine was converted to a polymer with a N, O-acetal structure, whereas at high heating temperatures, it was converted to a polymer with a Mannich structure because high temperatures allow the polymer to react with the SiH groups of PHPS. Measurements of synthesized poly[6, 6′-(1-methylethylidene)bis(3, 4-dihydro-3-2H-1, 3-benzoxazine)](PB-a)/silica nanocomposites showed that no reaction between PB-a hydroxy groups and PHPS SiH groups occurred because of a stepwise heating process. Measurements of synthesized poly[6, 6′-(1methylethylidene)bis(3, 4-dihydro-3-2H-1, 3-hexylbenzoxazine)] (PB-hda)/silica nanocomposites showed that no competitive reaction between PB-hda and PHPS occurred when materials were heated at 160 °C for 1 h because PB-hda formed no hydroxy group. Conversely, at 240 °C, a competitive reaction between PB-hda and PHPS occurred, which led to the formation of SiOC linkages. Graphical abstract: Highlights: Polybenzoxazine/silica nanocomposites were synthesized by ring opening polymerization of benzoxazines in the presence of perhydropolysilazane, PHPS, which is a silica precursor. Curing at 240 °C improved thermal stability of poly[6, 6′-(1-methylethylidene)bis(3, 4-dihydro-3-2H-1, 3-hexylbenzoxazine] (PB-hda)/silica nanocomposites because the sufficient SiOC linkages were formed by the reaction between hydroxy groups of PB-hda and SiH groups of PHPS compared to poly[6, 6′-(1-methylethylidene)bis(3, 4-dihydro-3-2H-1, 3-benzoxazine)](PB-a)/silica nanocomposites. The SiOC linkages were not formed in nanocomposites at low curing temperature, 160 °C, owing to the conversion of benzoxaine to the N, O-acetal structure. The SiOC linkages in nanocomposites started to be formed when the curing was carried out over 200 °C because of the competitive reaction between hydroxy groups of PB-hda and SiH groups of PHPS.